2020
DOI: 10.1186/s13018-020-01785-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of sensory corpuscles in human transplants of the anterior cruciate ligament

Abstract: Background Sensory nerve endings in ligaments play an important role for the proprioceptive function. Clinical trials show that the sense of body position does not fully recover in the knee joint after reconstructive surgery of the ruptured anterior cruciate ligament. The aim of this study is to identify sensory corpuscles in autogenous and allogenous transplants of the ligament and to compare their quantity between the used allografts and autografts. Methods Thirty-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…With increasing time from implantation, the MRCs, especially in the patellar tendon autografts, showed an increase in their number for both Ruffini and free nerve endings. The authors concluded that the partial increase in the number of receptors over time after ACL reconstruction could indicate a reinnervation of the grafts [ 8 ]. Another study histologically evaluated the presence of mechanoreceptors in Achilles tendon allografts at a mean 26.63 months after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing time from implantation, the MRCs, especially in the patellar tendon autografts, showed an increase in their number for both Ruffini and free nerve endings. The authors concluded that the partial increase in the number of receptors over time after ACL reconstruction could indicate a reinnervation of the grafts [ 8 ]. Another study histologically evaluated the presence of mechanoreceptors in Achilles tendon allografts at a mean 26.63 months after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Histological staining methods most commonly identify the structurally normal MRCs only, while the immunological stains identify the functionally viable MRCs [ 7 ]. Three antibodies are widely used in immunohistochemical analysis of neuronal structures and have proven to be the most reliable method in the detection of MRCs: the polyclonal antibody against S-100, the one against p75 and the monoclonal antibody against PGP9.5 [ 8 ].…”
Section: Proprioception—basic Sciencementioning
confidence: 99%
“…Another recent study corroborated these findings with immunohistochemical analyses showing little reinnervation of Ruffini corpuscles but greater distribution of free nerve endings in graft tissue after failure when compared with healthy ACL tissue after first-time rupture. 55 This indicates that somatosensory reintegration is scarce but that pain signaling may be enhanced in these patients. Interestingly, a series of studies demonstrated that following ACL injury, loss of somatosensory evoked potentials was actually linked with higher levels of functional outcomes even when proprioceptive deficits were present.…”
Section: Altered Somatosensation and Cortical Mechanismsmentioning
confidence: 99%